2005
DOI: 10.1159/000085147
|View full text |Cite
|
Sign up to set email alerts
|

In the Face of Pain: The Relationship between Psychological Well-Being and Disability in Women with Fibromyalgia

Abstract: Background: Few studies have examined the potentially beneficial role of positive psychological functioning in individuals with chronic pain. This study examined the relationship of psychological well-being (PWB) to pain and disability in women with fibromyalgia (FM) as compared to women with rheumatoid arthritis (RA) and healthy controls (HC). We targeted several domains of PWB that have been associated with health, and also tested whether PWB was related to the women’s social network. Methods: PWB, pain, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 103 publications
8
43
2
Order By: Relevance
“…Scleicher et al (2005) found a relationship between positive personal relationships and psychological well-being in female patients with fibromyalgia. 44 But the quality of social support does not seem to play an important role in health status, as measured in the present study. The finding that patients with positive situation-specific cognitions rated performance of activities of daily living as less difficult underscores the importance of self-efficacy, defined as beliefs (cognitions) that one can competently cope with a challenging situation and that one has the ability to influence behaviour in coping with symptoms of fibromyalgia.…”
Section: Discussioncontrasting
confidence: 68%
“…Scleicher et al (2005) found a relationship between positive personal relationships and psychological well-being in female patients with fibromyalgia. 44 But the quality of social support does not seem to play an important role in health status, as measured in the present study. The finding that patients with positive situation-specific cognitions rated performance of activities of daily living as less difficult underscores the importance of self-efficacy, defined as beliefs (cognitions) that one can competently cope with a challenging situation and that one has the ability to influence behaviour in coping with symptoms of fibromyalgia.…”
Section: Discussioncontrasting
confidence: 68%
“…This study employs mindfulness-based stress reduction (MBSR) [24] to evaluate whether an intervention that primarily focuses on psychosocial adjustment to and coping with chronic dysfunction [e.g. [25]] may provide long-term benefits for female fibromyalgia patients. MBSR has been employed among patients with a wide variety of chronic clinical ailments [26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have specifically focused on the effects of pain and function on emotional outcomes in women with FMS. Multiple studies have found depression is more prevalent in persons with FMS than persons with other chronic pain disorders (Haugli et al, 2004;Huber, Suman, Biasi, & Carli, 2008;Schleicher et al, 2005;Shuster et al, 2009;Tander et al, 2008). From these studies it appears the emotional upheaval experienced in persons with FMS is related to multiple factors.…”
Section: Uncertainty Client-hcp Communication and Swbmentioning
confidence: 98%
“…Although FMS may strike children, and men and women of all ages, the incidence is highest in middle-aged females (National Fibromyalgia Association [NFA], 2015;Weir et al, 2006). Importantly, FMS imposes a substantial burden, as it causes disability and impacts quality of life (Annemans et al, 2009;Egeli et al, 2008;Lempp et al, 2009;Robinson et al, 2012;Schleicher et al, 2005;Shuster et al, 2009). …”
Section: Modification Of Mishel's (1990) Ruitmentioning
confidence: 99%
See 1 more Smart Citation